Health‐related correlates of psychological well‐being among girls and boys 6–8 years of age: The Physical Activity and Nutrition in Children study. (3rd April 2018) - Ikävalko, Tiina; Lehto, Soili; Lintu, Niina; Väistö, Juuso; Eloranta, Aino‐Maija; Haapala, Eero A; Vierola, Anu; Myllykangas, Riitta; Tuomilehto, Henri; Brage, Soren; Pahkala, Riitta; Närhi, Matti; et al.
Abstract : Aim: Due to limited knowledge on the differences in the correlates of psychological well‐being (PSWB) between girls and boys, we compared the correlates of PSWB between primary school girls and boys. Methods: A population sample of 412 children participated in the Physical Activity and Nutrition in Children study. Parents completed a questionnaire that included 19 questions on the components of PSWB, and a PSWB score was computed. We assessed correlates of PSWB, including physical activity, sedentary behaviour, cardiorespiratory fitness, diet quality, body fat content, sleep duration, sleep disordered breathing, prevalent diseases and parental characteristics. We used logistic regression to analyse the risk of being in the lowest third of the PSWB scores. Results: Low parental education was associated with increased risk (odds ratio (OR) 2.34, P = 0.039) and high cardiorespiratory fitness with decreased risk (OR 0.26, P = 0.006) of poor PSWB in girls. At least 2 h of screen‐based sedentary behaviour per day (OR 1.93, P = 0.037), daily parental smoking (OR 2.10, P = 0.034) and sleep disordered breathing (OR 4.24, P = 0.003) were related to increased risk of poor PSWB in boys. Conclusions: There are large differences in the correlates of PSWB between girls and boys. Most of these correlates are modifiable and related to the health behaviour of children and their parents.